STRATEGI OPTIMALISASI DESAIN PENAMBANGAN MELALUI PENDEKATAN PARAMETER GEOTEKNIK - Andyono Broto Santoso (Institut Teknologi Sains Bandung, 2024)
The optimisation of mine design is strongly influenced by factors such as the price of raw materials and geotechnical parameters. Design decisions, which are ultimately determined by geotechnical conditions, are affected by fluctuations in commodity prices. The geotechnical conditions are important for the mine design to be responsive to changes in the geotechnical conditions. The modelling of geotechnical parameters is necessary in order to anticipate design changes that may be in the pipeline. Modelling is a comprehensive analysis incorporating accurate geotechnical parameters and considering material properties and rock conditions. The modelling process can use several existing methods. The main objective is to analyse the stability of the high wall slope. The focus of this analysis is on cohesion and internal friction angles, which take into account the physical and mechanical properties of the material. The analysis is carried out to determine the optimum safety factor value for a given geometry. The value of the safety factor is set at 1.2 by taking into account the correlation between the total slope and the height of the slope. This principle shows that the deeper the trench, the lower the total gradient. This correlation provides an advantage when reserve amounts change due to various factors. In this way, modelling using a geotechnical parameter approach can assist in optimising mining design while ensuring slope stability is maintained